Essential and non‐essential interactions in interactome networks: the Escherichia coli division proteins FtsQ–FtsN interaction. (19th June 2013) - Grenga, L.; Rizzo, A.; Paolozzi, L.; Ghelardini, P.; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary The Escherichia coli division protein FtsQ, which plays a central role in the septosome assembly, interacts with several protein partners of the division machinery. Its interaction with FtsB and FtsL allows the formation of the trimeric complex connecting the early cytoplasmic cell division proteins with the late, essentially periplasmic, ones. Little is known about the interactions that FtsQ contracts with other divisome components, besides the fact that all are localized in its periplasmic domain. In this domain, two independent subdomains, both involved in FtsQ, FtsI and FtsN interactions, were also identified. The study of FtsQ interaction‐defective mutants constituted a basis to investigate the biological significance of its interactions. However, in the case of interactions where two independent sites are involved, mutation(s) in one domain can be suppressed by the presence of the still‐functional second interaction region. To ascertain the biological role of these interactions, it is therefore necessary to select double mutants, where both sites are impaired. This paper describes the behaviour of FtsQ double mutants that have lost the ability to interact with FtsN, which is the last component in the hierarchy of divisome assembly, and is necessary to guarantee its stability and function.